EPEN-54. ACNS0831, PHASE III RANDOMIZED TRIAL OF POST-RADIATION CHEMOTHERAPY IN PATIENTS WITH NEWLY DIAGNOSED EPENDYMOMA AGES 1 TO 21 YEARS. (4th December 2020) - Smith, Amy; Onar-Thomas, Arzu; Ellison, David; Owens-Pickle, Emily; Wu, Shengjie; Leary, Sarah E S; Fouladi, Maryam; Merchant, Thomas; Gajjar, Amar; Foreman, Nicholas
Abstract: PURPOSE: The primary objective of this study is to determine the EFS and OS of children with gross total and near totally resected ependymoma (EPN) treated with post-operative focal radiation therapy (RT) followed by randomization to either RT alone or RT + 4 cycles of maintenance chemotherapy with vincristine, cisplatin, cyclophosphamide and etoposide. Secondary objectives include estimating the EFS and OS of children not randomized, evaluation of neurobehavioral and quality of life (QoL) endpoints, and EPN biomarkers. RESULTS: 479 patients enrolled, 451 were eligible. Of 325 eligible randomized patients, 161 were randomized to RT alone and 164 to RT + maintenance chemotherapy. Age range (1–21 years, median 4.9 years). The planned primary analysis was based on intent-to-treat, irrespective of actual treatment received. Based on the data available as of 12/31/2019, estimated 3-year EFS in the RT + maintenance chemotherapy vs. RT arms were 78% vs. 72%, respectively, which did not meet statistical criteria to establish the benefit of maintenance chemotherapy post RT (1-sided log-rank p-value=0.074). Due to significant noncompliance (30.5% in the RT + maintenance vs 4.3% in the RT arm), a planned secondary "as treated" analysis was performed. With median follow-up of 42.6 months among patients without events, the 3 year EFS estimates for patients who received any chemotherapy (n=114) vs. those who received RT only (n=196) were 80% vs. 71%, respectively (1-sided p-value = 0.0121). CONCLUSION: Early results in this randomized trial suggest that there may be some EPN patients who benefit from maintenance chemotherapy. Genomic analyses are ongoing.